2017
DOI: 10.1371/journal.pone.0170288
|View full text |Cite
|
Sign up to set email alerts
|

Association of lower urinary tract syndrome with peripheral arterial occlusive disease

Abstract: PurposeTo describe atherosclerosis may lead to chronic bladder ischemia, eventually resulting in lower urinary tract syndrome (LUTS), and peripheral arterial occlusive disease (PAOD). We investigated the association of LUTS with PAOD.MethodsThis nationwide population-based cohort study was based on data from the Taiwan National Health Insurance Database from 2000 to 2010; follow-up lasted until the end of 2011. We identified patients with newly diagnosed LUTS by using International Classification of Diseases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
0
16
2
Order By: Relevance
“…In support, Uzun et al also founds a positive correlation between patients with metabolic syndrome (ie, central obesity, hypertension, dyslipidemia, and hyperglycemia) and symptoms of OAB, suggesting that metabolic syndrome could be an etiologic pathway for the onset of OAB. Similarly, Lin et al found an increased likelihood of a broad spectrum of LUTS amongst adults with peripheral arterial occlusive disease from a cohort study of 72 084 adults.…”
Section: Discussionmentioning
confidence: 91%
“…In support, Uzun et al also founds a positive correlation between patients with metabolic syndrome (ie, central obesity, hypertension, dyslipidemia, and hyperglycemia) and symptoms of OAB, suggesting that metabolic syndrome could be an etiologic pathway for the onset of OAB. Similarly, Lin et al found an increased likelihood of a broad spectrum of LUTS amongst adults with peripheral arterial occlusive disease from a cohort study of 72 084 adults.…”
Section: Discussionmentioning
confidence: 91%
“…18 Patients were not required to have a diagnosis of OAB (International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) diagnosis codes 596.51; 596.59; 788.1x; 788.3x), as lower urinary tract symptoms are likely under-coded. 24 …”
Section: Methodsmentioning
confidence: 99%
“…Discontinuation of antimuscarinics may also have been confounded by comorbid conditions and medications; therefore, several comorbidities were examined using the Elixhauser Comorbidity algorithm, 24 modified to include medications used to treat hypertension, diabetes, and hypothyroidism. Other comorbid conditions diagnosed in older adults and comorbid conditions that may be associated with discontinuation of antimuscarinics, along with medications used to treat these conditions, including osteoporosis, Parkinson’s disease, glaucoma, high cholesterol, constipation, weakness, and falls were also assessed.…”
Section: Methodsmentioning
confidence: 99%
“…In clinical studies, Lin et al studied 36,042 patients and reported a significant correlation between LUTS and the prevalence of atherosclerotic arterial occlusive disease. 1 Gibbons et al reported that American Urological Association Symptom Score (AUA-SS) is significantly higher in patients with vascular disease risk factors in comparison with patients without vascular risk factors. 2 Other studies revealed low bladder blood flow in the elderly population and found a close correlation between decreased bladder perfusion and LUTS in both men and women.…”
Section: Introductionmentioning
confidence: 99%